110. The Burden and Preventability of Sepsis-Associated Mortality in 6 US Acute Care Hospitals. (26th November 2018) - Rhee, Chanu; Jones, Travis; Hamad, Yasir; Pande, Anupam; Varon, Jack; O'Brien, Cara; Anderson, Deverick J; Warren, David K; Dantes, Raymund; Epstein, Lauren; Klompas, Michael
Abstract: Background: Sepsis is considered a leading cause of preventable death, but the actual burden of sepsis mortality is difficult to measure using administrative data or death certificates. We analyzed the prevalence, underlying causes, and preventability of deaths due to sepsis in acute care hospitals using detailed medical record reviews. Methods: We randomly selected 577 adult patients who died in-hospital or were discharged to hospice in 2014–2015 at 6 US academic and community hospitals for medical record review. Cases were reviewed by experienced clinicians for sepsis during hospitalization (using Sepsis-3 criteria), terminal conditions on admission (defined using hospice-qualifying criteria), immediate and underlying causes of death, and suboptimal sepsis care (delays in antibiotics, inappropriate antibiotic therapy, inadequate source control, or other medical errors). The overall preventability of death was rated on a 6-point Likert scale (from definitely not preventable to definitely preventable) taking into account comorbidities, severity of illness, and quality of care. Results: Sepsis was present in 302/577 (52%) hospitalizations ending in death or discharge to hospice and was the immediate cause of death in 199 cases (35%) (Figure 1A). Underlying causes of death in sepsis patients included solid cancer (21%) and chronic heart disease (15%), and hematologic cancer (10%) (Figure 1B). The median age of sepsis patients who died was 73 (IQR 62–84). Terminal conditions were present in 122/302 (40%) sepsis deaths, most commonly end-stage cancer (26% of cases). Suboptimal care was identified in 68 (23%) of sepsis deaths, most commonly delays in antibiotics (11% of cases). However, only 4% of sepsis deaths were definitely or likely preventable and an additional 8% were considered possibly preventable with optimal clinical care (Figures 2 and 3). Conclusion: Our findings affirm that sepsis is the most common cause of death in hospitalized patients. Most patients that died with sepsis were elderly with severe comorbidities, but up to 1 in 8 sepsis deaths were felt to be potentially preventable with better hospital-based care. These findings may inform resource allocation and expectations surrounding the impact of hospital-based sepsis treatment initiatives. Disclosures: All authors: No reported disclosures.